PENGELOLAAN OBJEK WISATA PEMANDIAN AIR PANAS RANORAINDANG DIDESA LEILEM KECAMATAN SONDER - DEYSI MANGOWAL; FLORENCE LENGKONG; NOVIE PALAR (JURNAL ADMINISTRASI PUBLIK, 2022)
This study aims to determine the management of the Ranoraindang Hot Spring tourist attraction in LeilemVillage. The type of research used is qualitative research. This research utilizes the theoretical basis as a guide sothat the focus of research is in accordance with the facts on the ground, starting from the data, utilizing existingtheories as explanatory material and ending with a theory. Descriptive research in this study was conducted todetermine the Management of Ranoraindang Hot Springs Tourism Object in Leilem Village, Sonder District. Byusing 4 elements in management, namely: Planning (Planning) Related to the effectiveness of time planning, andprogram determination, Organizing (Organizing) Relating to effectiveness in grouping and division of tasks,Actuating (Implementation) Concerning the effectiveness or success in the implementation of each program thathas been planned, Controlling (Supervision) As a report of accountability and evaluation based on facts in thefield.Keywords: Management of Hot Springs Tourism Object, Government, and Society